Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1038/clpt.2010.307
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo-Controlled Trial of Sustained-Release Dextroamphetamine for Treatment of Methamphetamine Addiction

Abstract: Sixty treatment-seeking individuals with methamphetamine (MA) dependence entered a randomized, placebo-controlled, double-blind clinical trial of oral dextroamphetamine (d-AMP) as a replacement therapy for MA dependence. The subjects took 60 mg sustained-release d-AMP for 8 weeks, during which time they received eight 50-min sessions of individual psychotherapy. Adverse events and urine toxicology for MA were assessed two times a week. There were no serious adverse events. Urine samples containing <1,000 ng/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
73
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 46 publications
(46 reference statements)
7
73
1
1
Order By: Relevance
“…The general class of abused stimulants also includes drugs such as amphetamine, methamphetamine, and emerging cathinone analogs that function as substrates at dopamine transporters to promote dopamine release (Baumann et al, 2012a;Cameron et al, 2013;Rothman et al, 2001). Recent clinical trials and a human laboratory study found that amphetamine maintenance failed to produce significant decreases in methamphetamine consumption (Galloway et al, 2011;Longo et al, 2010;Pike et al, 2014). These and related results have been interpreted to suggest that dopamine releasers such as amphetamine may be more effective to treat abuse of dopamine uptake inhibitors (eg, cocaine) than abuse of other dopamine releasers.…”
Section: Investigate the Generality And Mechanisms Of Agonist Medicatmentioning
confidence: 99%
“…The general class of abused stimulants also includes drugs such as amphetamine, methamphetamine, and emerging cathinone analogs that function as substrates at dopamine transporters to promote dopamine release (Baumann et al, 2012a;Cameron et al, 2013;Rothman et al, 2001). Recent clinical trials and a human laboratory study found that amphetamine maintenance failed to produce significant decreases in methamphetamine consumption (Galloway et al, 2011;Longo et al, 2010;Pike et al, 2014). These and related results have been interpreted to suggest that dopamine releasers such as amphetamine may be more effective to treat abuse of dopamine uptake inhibitors (eg, cocaine) than abuse of other dopamine releasers.…”
Section: Investigate the Generality And Mechanisms Of Agonist Medicatmentioning
confidence: 99%
“…Numerous clinical trials have investigated the ability of DA reuptake inhibitors and releasers to treat cocaine AMPH dependencies. At least some studies demonstrate that DAT inhibitors are more effective than DA releasers for reducing use of DA releasers (Grabowski et al, 1997;Tiihonen et al, 2007), whereas DA releasers are more effective than DAT inhibitors for reducing use of DA inhibitors (Grabowski et al, 2001;Mooney et al, 2009;Longo et al, 2010;Galloway et al, 2011). For example, the DAT inhibitor MPD has been tested as a putative agonist replacement therapy for cocaine and METH/ AMPH dependence.…”
mentioning
confidence: 99%
“…Fourth, the participants in the present study were non-treatment seeking stimulant users and it is possible that damphetamine could produce greater reductions in methamphetamine use in a population that is seeking treatment, as the participants in the present study did not have any intention of decreasing their stimulant use. Non-treatment seeking stimulant users were enrolled in the present study due to ethical considerations of providing individuals who are seeking treatment with methamphetamine, but d-amphetamine has been tested in clinical trials to reduce methamphetamine abuse in treatment seeking populations and did not produce significant reductions in methamphetamine use (18,19). Fifth, demographic variables could have impacted the results of the study, as the sample size was small, which is supported by previous analyses of treatment responders in clinical trials (20).…”
Section: Discussionmentioning
confidence: 51%
“…The trend toward a decrease in self-administration of the lowest dose of methamphetamine during d-amphetamine maintenance compared to placebo maintenance supports this notion. However, higher doses, up to 110 mg/day have been tested in previous clinical trials and did not significantly reduce methamphetamine use compared to placebo (18,19), which suggests that the lack of a reduction of self-administration of methamphetamine during damphetamine maintenance may not be solely due to the dose tested. Second, methamphetamine was insufflated.…”
Section: Discussionmentioning
confidence: 99%